Psoralen, a mechanism-based inactivator of CYP2B6. (5th October 2015) - Ji, Lin; Lu, Dan; Cao, Jiaojiao; Zheng, Liwei; Peng, Ying; Zheng, Jiang
Abstract: Furanocoumarin compound psoralen (PRN) is a major active ingredient found in herbaceous plants. PRN has been used for the treatment of various dermal diseases in China. We evaluated the inhibitory effect of PRN on cytochrome P450 2B6 (CYP2B6) and found that PRN induced a time-, concentration-, and NADPH-dependent inactivation of CYP2B6 with the values of K I and k inact being 110.2 μM and 0.200 min −1, respectively. Ticlopidine, a CYP2B6 substrate, prevented the enzyme from the inactivation induced by PRN. Exogenous nucleophile glutathione (GSH) and catalase/superoxide dismutase showed limited protection of CYP2B6 from the inactivation. The estimated partition ratio of the inactivation was approximately 400. GSH trapping experiments indicates that an epoxide or/and γ -ketoenal intermediate was formed in microsomal incubations with PRN. In summary, PRN was characterized as a mechanism-based inactivator of CYP2B6. Highlights: Psoralen (PRN) is a mechanism-based inactivator of CYP2B6. A γ -ketoenal intermediate was identified in rat liver microsomes after exposed to PRN. The γ -ketoenal intermediate may be responsible for the enzyme inactivation. CYPs 1A2, 2B6, 2C19, and 2D6 are the major enzymes responsible for the metabolic activation of PRN.